Forced intercourse in America: a pandemic update - William G. Axinn; Brady T. West; Heather M. Schroeder (BMC, 2023)
Abstract Background Measures of forced intercourse from the U.S. National Center for Health Statistics (NCHS) indicate high prevalence among U.S. women, which is likely to produce unintended pregnancies. However, NCHS did not measure forced intercourse during the pandemic, limiting knowledge of recent prevalence rates. Methods We use multiple nationally-representative, cross-sectional surveys representing the U.S. population from 2011 to 2022 to document these trends. This includes measures from the National Survey of Family Growth, the Panel Study of Income Dynamics Transition into Adulthood Supplement, and the American Family Health Study (AFHS) to provide population estimates of forced intercourse. Results Reports of forced intercourse remained high during the pandemic, with more than 25% of U.S. females over 40 reporting lifetime forced intercourse in the AFHS (number of females in AFHS: 1,042). There was a significant increase among females aged 24-28 (p < 0.05) and rates are highest for those who did not complete college. Among females 24-28, 32.5% (S.E. = 5.7%) with less than 4 years of college reported forced intercourse, a significantly (p < 0.05) higher rate than among those with a higher level of education. Conclusions Rates of forced intercourse among U.S. women remained high during the pandemic, increasing significantly in early adulthood. This exposure to forced intercourse is likely to produce an increase in unintended pregnancies and other sexual, reproductive, and mental health problems.